FEATURES OF THE TECHNOLOGICAL COMPONENT OF THE IVANOVO REGION HEALTH SYSTEM POLICY IN MALIGNANT TUMORS EARLY DIAGNOSIS - V. A. Kozlov; B. A. Polyakov; D. L. Mushnikov; E. L. Funtikova; D. L. Nedavny (Исследования и практика в медицине)
Purpose of the stydy. To study the Features of the technological component of the Ivanovo region health system policy in malignant tumors early diagnosisMaterials and methods. The base of the research is the Ivanovo Regional Oncology Dispensery, Department of Health of the Ivanovo Region. Methods: sociological, expert assessment, analytical, documentary. The assessment of the technological component of oncological service policy was carried out in the three areas: a) an assessment of the quality of oncological assistance using the method of correspondence examination of completed cases of assistance with filling out expert assessment cards (600 cases of assistance); b) an assessment of patients' satisfaction with the help provided by the method of a sociological questionnaire survey (600 patients); c) an assessment of the apparent patients' dissatisfaction with the help provided based on the analysis of justified complaints (30 people).Results. The expertize of oncological medical services provided showed that there is a decrease in a number of its properties in modern conditions. The first ranking places in terms of the frequency of violations belong to the following properties of medical services quality: timeliness; adequacy; continuity; performance, availability. In the structure of medical and organizational defects in the quality of care, according to the results of expert evaluation, the leading part of them- 70.5% — is occupied by diagnostic defects (non-compliance by the medical personnel with the oncological screening standard, non-use of instrumental and laboratory research methods).Conclusion. The policy of oncological care quality has signs of decrease (the number of diagnostic and medical-organizational defects averages 1.7 for each case of diagnosed cancer), which leads to advanced cases of oncopathology. The results of the study showed that the current system of oncological care in modern conditions is not sufficiently effective and requires improvement, including by increasing the doctors' level of cancer alertness, increasing the efficiency of the regional cancer pathology commissions.